2012
DOI: 10.1159/000342141
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Is an Independent Biomarker of Severe Traumatic Brain Injury Prognosis

Abstract: Background: Cytokines have been shown to be involved in traumatic brain injury (TBI). We investigated the independent association between serum levels of IL-10 and TNF-α and hospital mortality of patients with severe TBI. Methods: Serum IL-10 and TNF-α levels were determined after a median period (interquartile range (IQ) 25–75) of 10 h (IQ 5–18) after severe TBI in 93 consecutive patients and in randomly selected patients with mild (n = 18) and moderate (n = 16) TBI. In patients with severe TBI, additional bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 53 publications
5
41
0
1
Order By: Relevance
“…Interleukin-10 has been shown to be elevated in TBI patients (78, 133135) and has been associated with unfavorable outcome and mortality (75, 134, 135). Despite these associations, Chen et al found a role for IL-10 in conferring neuroprotection with hyperbaric oxygen (HBO) treatment (80).…”
Section: Inflammatory Mediators In Tbimentioning
confidence: 99%
“…Interleukin-10 has been shown to be elevated in TBI patients (78, 133135) and has been associated with unfavorable outcome and mortality (75, 134, 135). Despite these associations, Chen et al found a role for IL-10 in conferring neuroprotection with hyperbaric oxygen (HBO) treatment (80).…”
Section: Inflammatory Mediators In Tbimentioning
confidence: 99%
“…Statistical models which combine two or more variables of patient data to predict clinical outcome (also called prognostic models) have been applied to TBI research [5,6,28,29]. The investigation associated with prognosis may help in medical decisions, as well as identifying possible therapeutic targets for the patients [30][31][32]. The association between hormones and TBI prognosis can be affected by several confounding variables in the context of critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective single-center study of 93 patients with GCS<9 following TBI found interleukin-10 (IL-10) to be an independent predictor of severe TBI prognosis. Elevated serum IL-10 correlated significantly with GCS severity and with hospital mortality in patients with severe TBI [42].…”
Section: Research Innovations: Biomarkersmentioning
confidence: 91%